Gerenciamento de resíduos sólidos de uma indústria gráfica com enfoque em produção mais limpa (p+l) : estudo de caso no Espírito Santo - Kaminice, Paulo Vitor Reis (2017)
Solid waste generation in the printing industries represents a serious problem, as well as being related to the reduce production performance, increase of production costs, material losses and also environmental aspects and impacts. The industrial production optimization is a decisive factor for competitiveness, anchored in the Brazilian Solid Waste Law (nº 12.305/2010). Solid Waste Management Plan has become corporate strategy for industrial pollution prevention and correlates into optimization actions and continuous improvement in industrial process, associated to cleaner production (CP) methods and sustainable production practices. Therefore, the purpose of this research was, by the case study, to diagnose solid waste management focusing cleaner production methodology and legal prerogatives, also implement a solid waste management plan. All productive processes was evaluated at printing industry, aiming the opportunity to understand the importance of continuous improvement processes based on the environmental and economic impacts reduction, resulting in the adoption of ecoefficient values, best operational and organizational culture practices, adding economic value to the final product, such as functional value at printing industry production process. Waste Management Plan contribution can be observed by the positive performance in the industrial process, which resulted in an optimization between the consumption of raw materials and solid waste generation, adding greatervalue to the product and also the addition of financial resources through recyclable solid waste sales. The synergy between waste management plan and cleaner production methodology improves the environmental performance, operational performance and optimizated production process at printing industry. The results suggest that printing industries and other industrial sector explore the methodology adopted, integrating cleaner production with waste management plan, developing an integrated environmental management system tool.